The Level of Readiness of Islamic Education Teachers in Kelantan Islamic Foundation Secondary School Toward Multimedia Platform in Teaching / Tahap Kesediaan Guru Pendidikan Islam di Sekolah Menengah Yayasan Islam Kelantan Terhadap Multimedia Dalam Pengajaran (Sains Humanika, 2020)
This study aims to survey the level of readiness of Islamic education teachers toward multimedia platform in teaching, also the difference of the level of readiness based on the demography of GPI. The study involved 127 Islamic education teachers who taught subjects under Islamic education such as Quranic and as-Sunnah Education, Shariah Islamic Education and Tasawwur Islamiah in Kelantan Islamic Foundation secondary school. The quantitative data of the questionnaires instrument were analysed descriptively using the Statistical Package for the Social Sciences (SPSS) version 25 to obtain the frequency, percentage, mean, interpretation and standard deviation while inference analysis using t-Test, one-way ANOVA test and Post hoc Scheffe test. The findings from the level of readiness such as level of knowledge, level of skill and level of attitude showed a high level of moderation (min=3.70, sp=0.62). The inferential analysis also showed that there was a significant difference (p
Keywords: The level of readiness; Islamic education teachers; Kelantan Islamic Foundation secondary school; multimedia platform in teaching